Advance tennis - Metzler, Paul (New York : Collier Books, 1972)
There are thousands of advanced players besides the professionals and internationals. If you play tennis regularly - competitively or otherwise-you are one of them. Tennis is not your living, so you play it on Saturdays and Sundays.
Foreword -- Introduction -- Temperament -- Watching and controlling the ball -- Getting to grips with your opponent's game -- Training your big guns -- Effective ground strokes -- Volleys, drop shots, lobs -- Footwork, scrambling, stroking -- In the face of obstacles -- Effective doubles -- Points-particular and sundry -- Parting shots -- Index